SIKAP DAN KEPUASAN KONSUMEN RUMAH MAKAN “XXX” LAMONGAN DI BANDAR LAMPUNG - Rinty Azaria; Sudarma Widjaya; Maya Riantini (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to explore the consumers’ attitudes and satisfaction toward restaurant. This research is conducted at "XXX" Lamongan Restaurant in Bandar Lampung. Data collection was carried out in January-February 2019 by the case study method employing the number of respondents of 60 people who were selected by nonprobability sampling method. The data were analyzed using Multiatribut Fishbein Model, Customer Satisfaction Index and Importance Performance Analysis. The results of this research showed that food taste has the highest score of consumers attitude toward restaurant. The satisfaction level of the restaurant has the value of 83.73%, included to the very satisfied category. The restaurant has been implementing the product attributes that were suitable with consumers’ wishes.Key words : consumer, restaurant, satisfaction